Analysis of The Value Added Smoked Catfish In Bawan Village Ampek Nagari Nagari Subdistrict Agam District West Sumatra Province (Case: Fogging Business Panca Usaha) - Mulyadi '; Hendrik '; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This study was conducted in january 2017 which located in business fogging Panca Usaha Bawan village Ampek Nagari subsdistrict Agam district West Sumatra province. This study aims to to analyze the cost, income and added value of processing enterprises catfishes be catfish smoke in business fogging Panca Usaha. The costs by efforts fogging catfishes Panca Usaha as much as Rp 1.733.917,- in once production. The income business fogging Panca Usaha consists of gross income (output value) much as Rp 23.310,- per kilogram raw materials with the profit obtained as much as Rp 6.060,- per kilogram raw materials. Added value produced business fogging Panca Usaha as much as Rp 8.660,- per kilogram to a ratio added value fogging catfishes of 37,15 %.Keywords: cost, profit, value added, fogging, Panca Usaha